PLANT BLINDNESS JUGA MENYERANG MAHASISWA PENDIDIKAN BIOLOGI: STUDI KASUS PRA-PERKULIAHAN DAN PASCA-PERKULIAHAN TAKSONOMI TUMBUHAN - Fadhlan Muchlas Abrori (Biopedagogia, 2020)
This study aims to identify cases of plant blindness in students of the Biology Education Study Program, University of Borneo Tarakan. The research was carried out pre and post the Plant taxonomy course. This research is a descriptive study, where the measurement of the level of student's plant blindness presents 20 types of plants around the University of Borneo Tarakan. The results showed that 15 types of plants could not be recognized well, with a truth level below 50%. However, after taking the plant taxonomy lecture, students recognized all 20 plant species with a level of truth above 90%.Keywords:  Plant Blindness, Biology Education